2022
DOI: 10.2337/dc22-0783
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hyperglycemia Drives the Risk of Hospitalization for Chest Pain in Patients With Ischemia and Nonobstructive Coronary Arteries (INOCA)

Abstract: OBJECTIVE Ischemia with nonobstructive coronary arteries (INOCA) is a prevailing finding in patients with angina. However, the main factors underlying the risk of being rehospitalized for chest pain in patients with INOCA remain mostly unknown. RESEARCH DESIGN AND METHODS We evaluated INOCA patients referred to the “Casa di Cura Montevergine” in Mercogliano (Avellino), Italy, from January 2016 to January 2021 for percutaneous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Numerous clinical studies have also indicated a link between SHR and unfavorable outcomes in AMI patients [21,22,35,36]. Pasquale et al also found that SHR significantly increases the risk of rehospitalization among 2,874 patients with ischemia with non-obstructive coronary arteries [37]. Given that SHR was used as an indicator for predicting future clinical events in patients with cardiovascular disease, it is still unclear whether it can effectively predict the risk of clinical outcomes in the MINOCA population.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have also indicated a link between SHR and unfavorable outcomes in AMI patients [21,22,35,36]. Pasquale et al also found that SHR significantly increases the risk of rehospitalization among 2,874 patients with ischemia with non-obstructive coronary arteries [37]. Given that SHR was used as an indicator for predicting future clinical events in patients with cardiovascular disease, it is still unclear whether it can effectively predict the risk of clinical outcomes in the MINOCA population.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Mone et al . [ 24 ] showed that the risk of re-hospitalization with chest pain is significantly increased in patients with ischemia and nonobstructive coronary arteries who have a SHR > 1 for 1 year, suggesting that the SHR may be used as an independent risk factor for these patients. Additionally, the SHR has been identified as a potential predictor for death in patients with MI, especially in those without DM [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (34) noted that the increase in the stress hyperglycemia plays an important role in predicting poor prognosis of patients with coronary heart disease undergoing percutaneous coronary intervention. For angina patients diagnosed as ischemia with nonobstructive coronary arteries, SHR at admission can significantly increase the risk of rehospitalization for chest pain (35). Given that the essence of coronary heart disease is atherosclerosis, it further suggests that the increase in the stress hyperglycemia may be involved in the rupture of atherosclerotic plaques and lead to hospital reinfarction for stroke patients.…”
Section: Discussionmentioning
confidence: 99%